Effect of Haloperidol on the Numerical Density of Neurons and Nuclear Height in the Rat Hippocampus - Ünal, B.; Özbek, M.E.; Aydin, M.D.; Aydin, N.; Bulucu, Z.; Vuraler, Ö.; Odaci, E. (Wiley, 2004)
In recent studies, some neuroleptics have shown neurotoxic activities. Clinical and experimental studies have been carried out to investigate the effects of different neuroleptic drugs considered to affect the central nervous system. The aim of this study was to evaluate neurotoxic effects of haloperidol on hippocampal neurons. The drug was given in daily doses of either 1 or 3 mg/ kg for 6 weeks to adult male guinea pigs. After treatment, all animals were anaesthetized via short inhalation of ether, and then were fixed by a mixture of 2% glutaraldehyde and +2% paraformaldehyde in 0.1 M phosphate buffer. Brains were removed from the cranium and stored in the same fixative overnight. On the following day, the CA1 region of the hippocampus was dissected out. After embedding in araldite resin and obtaining semi-thin sections, the tissues were stained with toluidine blue. The physical disector was used for measurements of nuclear height and numerical density of neurons and the sections were also evaluated histopathologically. The numerical density of neurons and nuclear height in the hippocampus for the low-dose (1 mg/kg) and high-dose (3 mg/kg) experimental groups were 12.4 mm3 and 3.6 μm and 7.14 mm 3 and 3.56 μm, respectively. In contrast, the control group had a neuronal numerical density of 16.55 mm-3 and a nuclear height of 4. 09 μm. There was a significant difference in both the mean density of neurons and the mean height of nuclei between haloperidol-treated and control groups (p<0.05). There was also a statistical difference in the mean density of neurons (but not in nuclear height) when comparing the dosage of haloperidol (p<0.05). These findings suggest that haloperidol treatment may lead to a loss of neurons as well as a decrease in the height of nuclei in the hippocampus.
Keywords: Haloperidol; Hippocampus; Neuron Density; Nuclear Height; Stereology